Training Needs Analysis In Competency Improvements To Support Employee Performance (Case Study Of A Logistics Company In The Field Of Ship Agency) - Ma’shumah Az Zahra; Mochamad Chairul Ihsan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The increasingly dynamic development of the logistics industry requires shipping agencies to have competent, adaptive human resources who are able to respond to operational complexities. However, employee training is often not fully based on actual needs in the field. This study aims to identify the training needs of employees in the Operations Department and formulate appropriate training recommendations to address competency gaps. This study uses a qualitative approach with in-depth interviews with key informants in the Operations and Human Capital Departments. The analysis concept used is Training Needs Analysis (TNA) according to McGehee and Thayer, which includes organization, operation, and individual analysis. The data was analyzed using thematic analysis through six stages with the help of NVivo software. The results of the study indicate a competency gap in soft skills and hard skills, which is influenced by high workloads, limited human resources, and the dynamics of port systems and regulations. Based on these findings, this study formulated priority training recommendations using the Eisenhower Decision Matrix to determine the urgency and importance of training. This study is expected to serve as the basis for more systematic, contextual, and sustainable training planning for shipping agencies.